Sigtuna Think Piece 6: A Case of Exploring Learning Interactions in Rural Farming Communities of Practice in Manicaland, Zimbabwe - Tichaona Victor Pesanayi (Environmental Association of Southern Africa, 2009)
Food insecurity is one of the major threats to sustainable development in Africa, and particularly southern Africa. Climate change is increasingly having negative impacts on food production, further increasing the vulnerability of resource-poor communities. This paper outlines a research study conducted in two Zimbabwean smallholder communities of practice, with the aim of understanding learning interactions taking place within the community of practice that influence its choice of cultivated food plants. This would hopefully inform capability-centred teaching and learning. The study was conducted in the context of vulnerability to environment risk, socio-political pressures and a market-oriented agro-based economy in recession. Various causal mechanisms influencing plant-food choice were identified using critical realist ontological analysis. These included mixed messages from external influences in conflict with local knowledge due to power knowledge relationships. A number of learning interactions were found to be important in promoting the adaptive capacity of the farmers to chronic drought, which included inter-generational knowledge sharing; farmer to farmer exchange and reflective dialogue; experiential learning; farmers 'passing on' part of their harvests to other farmers; farming communities learning from risk and responding to risk; and learning from trying things out. The implications for capability-centred social learning processes were that it is important to understand the causal mechanisms that influence choices; and to confront tensions, while reducing ambivalence. A focus on more sustainable alternatives, feasible and practical for farmers, was recommended. These findings, in the context of one case study, create research questions to be examined in other case contexts in environmental education research focusing on climate change learning and adaptation